DIFFERENCES IN EFFECTIVENESS OF OCIMUM-SANCTUM 4% GEL AND 25% METRONIDAZOLE GEL POST SCALING ROOT-PLANING IN CHRONIC PERIODONTITIS - Karina, Vincensia Maria; Lastianny, Sri Pramestri; Meiliyanawaty, Rina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Chronic periodontitis is a disease that causes inflammation of the tooth supporting tissue, loss of periodontal attachment, and loss of alveolar bone. Root planning scaling treatment is carried out to remove irritants and microorganisms. The use of additional materials is required when the pocket depth is more than 5 mm. One of the herbal ingredients that has the potential as an adjunct to periodontal therapy is the 4% ocinumsanctum.Method: The sample consisted of 20 periodontal pockets with a depth of 4-6 mm which were given scaling root planning which were divided into two groups, namely 10 pockets given 4% maximum sanctum gel and 10 pockets given Metronidazole gel 25%. evaluations of the papillary bleeding index, TNF-Î±, and IL-Î² were performed at baseline, and on day 21. TNF-Î± and IL-Î² levels were taken through the gingival sulcus fluid and then tested using ELISA.Result: Papillary bleeding index, TNF-Î±, and IL-Î² levels showed a significant reduction in both groups but there was no significant difference between the 4% ocimum sanctum group and Metronidazole gel.Conclusion: ocimum sanctum application 4% post scaling root planning was able to lower papillary bleeding index score, TNF-Î± levels, and IL-Î².